From philosophy to practice - Jaszczak, Agnieszka (Revija za geografijo, 2025)
This paper examines the philosophy and principles of the Citta Slow (Slow City) movement, which promotes a mindful and measured lifestyle in small urban environments. It explores how towns worldwide adopt these principles to strengthen community identity, preserve local traditions, and support environmental awareness. The study focuses on the Supra-Local Revitalization Program in selected towns in the Warmia and Mazury region of Poland, highlighting public space projects aligned with the movement's values. Special attention is given to the role of greenery in urban planning, showing how green infrastructure improves aesthetics, fosters social cohesion, and enhances environmental resilience. The paper offers insights into the practical benefits of applying Citta Slow principles for sustainable urban revitalization.
Keywords: Citta Slow; community identity; green infrastructure; identiteta skupnosti; Mala mesta; nadlokalni program revitalizacije; public space revitalization; revitalizacija javnega prostora; supra-local revitalization programe; sustainable urbanism; trajnostni urbanizem; Urbanizem; zelena infrastruktura